2010
DOI: 10.1097/prs.0b013e3181c2bb9d
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing the Potential of the Free Fibula Osteoseptocutaneous Flap in Mandible Reconstruction

Abstract: Efficient interdisciplinary communication and teamwork are necessary throughout the longitudinal care of the patient if optimal results are to be achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
89
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(94 citation statements)
references
References 70 publications
0
89
1
4
Order By: Relevance
“…The use of a double-skin paddle FFF has also been proposed as a safe and reliable way to reconstruct through-and-through anterior resections with large cutaneous defects. 2,5 Despite its limitations, the main advantage of the FFF is its unmatched sculptability. The straight bone lends itself to the replacement of lateral segments, or can be recontoured in cases of central defects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of a double-skin paddle FFF has also been proposed as a safe and reliable way to reconstruct through-and-through anterior resections with large cutaneous defects. 2,5 Despite its limitations, the main advantage of the FFF is its unmatched sculptability. The straight bone lends itself to the replacement of lateral segments, or can be recontoured in cases of central defects.…”
Section: Discussionmentioning
confidence: 99%
“…Additional benefits include the donor site location which allows for 2 teams to work concurrently and acceptable donor site morbidity. 2 In general, the FFF is the primary choice for reconstructing anterior mandibular defects, because the skin island can be rotated across to cover the floor of the mouth and the flexor hallucis longus muscle used to fill space around the mandible and upper neck. For lateral defects, the ilium, radius, scapula, or fibula may be chosen depending on the degree of resection.…”
Section: Discussionmentioning
confidence: 99%
“…The vascularized free fibula flap is the most versatile and reliable option for the microsurgical reconstruction of large mandibular defects (Wallace et al, 2010). The fibula flap was introduced in 1975 (Taylor et al, 1975), and Hidalgo confirmed in 1989 that it could withstand multiple osteotomies and successfully recreated the subtle mandibular contour (Hidalgo et al, 1989).…”
Section: ⅲ) Fibula Flapmentioning
confidence: 99%
“…Fibula osteocutaneous flaps provide up to 25 cm of bone and a skin paddle as large as 10-20 cm (Wang et al, 2011). The bone stock of the fibula flap combined with its bicorticocancellous structure make it excellent for the placement of osseointegrated implants (Wallace et al, 2010;Barber et al, 1995). The thin and pliable skin paddle can also be harvested as a neurosensory flap, and a vascularized nerve graft can be harvested with the fibula flap (O'Leary et al, 1994).…”
Section: ⅲ) Fibula Flapmentioning
confidence: 99%
See 1 more Smart Citation